Power system analysis - Nagsarkar, T. K.; Sukhija, M. S. (Oxford University Press, 2014)
The second edition of 'Power System Analysis' serves as a basic text for undergraduate students of electrical engineering. It provides a thorough understanding of the basic principles and techniques of power system analysis as well as their application to real-world problems.
Keywords: Electric power systems.; System analysis.; elektronické knihy; electronic books